2012
DOI: 10.1111/liv.12050
|View full text |Cite
|
Sign up to set email alerts
|

Portal, but not lobular, macrophages express matrix metalloproteinase‐9: association with the ductular reaction and fibrosis in chronic hepatitis C

Abstract: These findings demonstrate significant regional differences in macrophage phenotypes, suggesting that there are at least two populations of liver macrophages. We propose that these populations have distinct contributions to the pathogenesis of chronic HCV-related liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 49 publications
7
46
0
2
Order By: Relevance
“…In rodent models of ongoing liver injury, macrophages/KCs play a key role in the hepatic response to chronic inflammation [62]. The pattern of expression of membrane receptors and antigens like CD68 has been shown to reflect the state of and a-R-lipoic acid (F).…”
Section: Discussionmentioning
confidence: 99%
“…In rodent models of ongoing liver injury, macrophages/KCs play a key role in the hepatic response to chronic inflammation [62]. The pattern of expression of membrane receptors and antigens like CD68 has been shown to reflect the state of and a-R-lipoic acid (F).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, clinical studies discovered a link between the increased levels of MMPs, including MMP-9, and fragments of type-IV collagen in cirrhosis. 53 Furthermore, liver MMP-9 expression and activity have also been associated with the stage of fibrosis in chronic hepatitis C. 54 In a study conducted by Kamari and colleagues, 4 decreased liver fibrosis in interleukin-1 (IL-1) α-deficient mice fed with atherogenic diet (high-fat/cholesterol and cholate diet, HFHCD) was associated with lower MMP-9 expression independent of liver steatosis. These results, together with our present findings, illustrate the positive association between MMP-9 expression and liver fibrosis in response to high-cholesterol/cholate consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In Addition to elevated pro-inflammatory cytokines, it was observed that metabolic dysfunctions such as insulin resistance are associated with reduced protective adipokines (such as adiponectin (Hotta et al, 2000)), and increased macrophage accumulation in the liver and adipose tissue (Lanthier et al, 2010). In particular, CD4 (þ) and CD8 (þ) T cells infiltration increases in the liver (Gadd et al, 2013). Nevertheless, the mechanisms of the inflammatory response related to MetS are far from been completely elucidated.…”
Section: Inflammation and Er Stress Induce Insulin Resistance In Metsmentioning
confidence: 99%